The Influence of Transformational Leadership and Organizational Culture on Civil Servant Motivation - Sriwahyuni, Iranda; Yasmin, Devi (Eduvest - Journal of Universal Studies, 2025)
This research explores how transformational leadership and organizational culture affect the motivation levels of civil servants working at the Pontianak City Library and Archives Service. Grounded in the premise that effective leadership and a constructive organizational culture are critical drivers of public sector performance, the research aims to identify the extent to which these variables impact employee motivation in this bureaucratic setting. Employing a quantitative associative approach, data were collected through structured questionnaires and interviews with agency leadership and staff, followed by statistical analysis including validity, reliability, linearity, multicollinearity, and multiple regression tests. The findings reveal that both transformational leadership and organizational culture significantly and positively affect employee motivation, both individually and simultaneously. The regression results show that organizational culture has a stronger impact (β = 0.556) compared to transformational leadership (β = 0.280). These results underscore the importance of fostering a strong organizational culture alongside effective leadership practices to enhance civil servant motivation. The study contributes to leadership and organizational theory in the public sector and offers practical implications for policy implementation and human resource development within government institutions. Future research may explore mediating variables such as job satisfaction, conduct comparative studies across regions, or examine the role of digital leadership in shaping motivation within bureaucratic environments.